Emphatic Consonants in the Adaptation of English Loanwords into Hasawi Arabic - Alrajhi , Mashael Abdullah (International Journal of Language and Literary Studies, 2024)
Loanword adaptation contributes to a better understanding of how phonology functions universally and cross-linguistically. The present study sheds light on the consonantal adaptation of English loanwords into Hasawi Arabic. It specifically investigates the occurrence of emphatic consonants in the adapted Hasawi forms. Although /t?/ and /s?/ are not part of the source (English) language inventory, it is an interesting phenomenon that they have emerged in the adapted forms of English loanwords by Hasawi speakers. The results revealed that the adjacency of a back vowel to the consonants /s/ or /t/ in the adapted forms triggered the emphasis of these consonants to their emphatic counterparts. The emphasis effect surfaced whether the vowel in the English loanword was a back vowel already and just triggered the emphasis effect, or the vowel was not attested in Hasawi Arabic vowel inventory and was mapped to a back vowel which, in turn, triggered the emphasis effect.